Coolie hut - Trinidad - (:unkn) unknown (My University, 2009)
Photo of East Indian family outside their hut.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rural families--Trinidad and Tobago; Huts--Trinidad and Tobago; Village communities--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; Dwellings--Trinidad and Tobago; East Indians--Trinidad and Tobago; Ajoupa